Ultra‑fast kinematic vortices in mesoscopic superconductors: the effect of the self‑field - Cadorim, Leonardo Rodrigues [UNESP]; Oliveira Junior, Alexandre de; Sardella, Edson [UNESP] (Nature Research, 2020)
In the present work, we have studied the crossover between type I and type II superconductivity on mesoscopic superconducting thin films by numerically solving the 3D Ginzburg-Landau equations. We determined the dependence on temperature of the critical Ginzburg-Landau parameter kc(d), below which the superconductor behaves as type I for a given thickness d of the film. The effect of the sample dimensions on this crossover was also investigated. Additionally, we report a novel giant vortex configuration with a local minimum of the magnetic field at the centre of the core. Finally, we present certain results suggesting that the vortex-vortex interaction is not monotonic, varying instead from long-range attraction to short-range repulsion.
Keywords: Superconductivity; Vortex matter; Time-dependent Ginzburg-Landau equations; Type-I superconductivity